2003
DOI: 10.1074/jbc.m305043200
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Description of the Effect of the Mutation Y49F on Human Glutathione Transferase P1-1 in Binding with Glutathione and the Inhibitor S-Hexylglutathione

Abstract: The thermodynamics of binding of both the substrate glutathione (GSH) and the competitive inhibitor S-hexylglutathione to the mutant Y49F of human glutathione S-transferase (hGST P1-1), a key residue at the dimer interface, has been investigated by isothermal titration calorimetry and fluorescence spectroscopy. Calorimetric measurements indicated that the binding of these ligands to both the Y49F mutant and wild-type enzyme is enthalpically favorable and entropically unfavorable over the temperature range stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
5
12
0
Order By: Relevance
“…The affinity for glutathione S-ethacrynic acid by wildtype protein is also an order of magnitude lower for the intermediate complex than for the final complex. 12 At equilibrium, the affinity of wildtype hGST A1-1 for GTX is also higher than that of wild-type hGST P1-1 (K d Z1.23 mM, 25 8C) 33 and of wild-type SjGST (K d Z1.6 mM, 25 8C). 39 The higher affinity of the former is due to the additional van der Waals contacts formed at the interface between its localised C-terminal region and the proteininhibitor complex.…”
Section: Functionmentioning
confidence: 98%
See 2 more Smart Citations
“…The affinity for glutathione S-ethacrynic acid by wildtype protein is also an order of magnitude lower for the intermediate complex than for the final complex. 12 At equilibrium, the affinity of wildtype hGST A1-1 for GTX is also higher than that of wild-type hGST P1-1 (K d Z1.23 mM, 25 8C) 33 and of wild-type SjGST (K d Z1.6 mM, 25 8C). 39 The higher affinity of the former is due to the additional van der Waals contacts formed at the interface between its localised C-terminal region and the proteininhibitor complex.…”
Section: Functionmentioning
confidence: 98%
“…This is consistent with NMR data indicating that the mobile C-terminal region in the apo wildtype protein samples alternative helix-like conformations, similar to those in ligand-complexed protein. 13 On the other hand, the large negative DH obs of complex formation between GTX and hGST P1-1 (K67.5 kJ/mol) 33 is a consequence of a ligand-induced folding of helix 2 at the activesite. 46 Since the binding of GTX to hGST P1-1 is not a rigid-body interaction, as previously suggested, 33 ligand-induced folding of helix 2 could contribute as much as K20 kJ/mol to the overall enthalpy term.…”
Section: Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental conditions and data analysis were similar to those described elsewhere (Té llez-Sanz et al, 2006;Quesada-Soriano et al, 2009). The binding of active site ligands to the C47S/Y108V GST P1-1 mutant quenches the intrinsic fluorescence of the enzyme as was described for wt GST P1-1 Ortiz-Salmeró n et al, 2003;Caccuri et al, 1991). Equilibrium unfolding/refolding experiments were performed as described (Aceto et al, 1992) at 258C in 20 mM sodium phosphate buffer, pH 7, containing 0.1 mM EDTA and 1 mM DTT.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…This information is very valuable in drug design and cannot be obtained from structural or computational methods alone. In the first example we show the thermodynamics of binding of the substrate glutathione (GSH) and the competitive inhibitor S-hexylglutathione to the wt-enzyme and the Y49F mutant of the human glutathione S-transferase (hGST P1-1) (Ortiz-Salmerón et al, 2003). Structural studies revealed that two residues (Cys 47 and Tyr 49) located in a mobile helix, denoted as 2, could participate in intersubunit communication between active sites of the dimer.…”
Section: Evaluation Of Protonation Effects In Binding Processesmentioning
confidence: 99%